Reduction in Gaps in High CD4 Count and Viral Suppression Between Transgender and Cisgender Persons Living With HIV in New York City, 2007–2016 - Xia, Qiang (Am J Public Health, 2019)
Objectives. To compare trends in HIV outcomes for cisgender and transgender persons living with HIV (PLWH) in New York City. Methods. We used HIV surveillance data for the analysis. We based CD4 count on the last measurement in a calendar year and defined viral suppression as the last viral load being less than or equal to 200 copies per milliliter in the calendar year. Results. The estimated number of PLWH increased from 73 415 in 2007 to 83 299 in 2016, including 606 transgender persons (0.8%) in 2007 and 1054 transgender persons (1.3%) in 2016. The proportion with CD4 count of 500 cells per cubic millimeter or more increased from 38% in 2007 to 61% in 2016 among cisgender persons versus 32% to 60% among transgender persons. The proportion with a suppressed viral load increased from 52% in 2007 to 80% in 2016 among cisgender persons versus 42% to 73% among transgender persons. Conclusions. Among PLWH in New York City, CD4 count and viral suppression improved during 2007 to 2016, with larger improvements among transgender persons, leading to narrower gaps. However, continuing efforts to improve HIV outcomes among transgender PLWH are needed to further eliminate disparities, particularly in viral suppression.